The effect of educational interventions by nurses through Orem’s self-care theory on the ability of self-care in myocardial Infarction patients in public sector hospital: a quasi-experimental study - Muhammad Shahid; Masih, Sarfraz; Lashari, Nawaz; Farooqui, Waqas Ahmed (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the impact of educational intervention by nurses guided by Orem’s theory to reinforce the of self-care abilities of patients experiencing myocardial infarction. Method: The prospective, quasi-experimental case-control study was conducted from September 2020 to April 2021 at Dr. Ruth K.M. Pfau Civil Hospital, Karachi, and comprised myocardial infarction and heart failure patients with co-morbidities diabetes mellitus and hypertension. The patients were randomised into experiment group A and control group B. Group A received educational intervention one day before and one day after discharge in line with the American Heart Association guidelines. Two 30-45-minute sessions of seven modules were conducted. Group B received routine information from ward staff. Assessment was done at baseline and first month and second month post-intervention using the Heart Failure Self-Care Index version 6.2. Data was analysed using SPSS 20. Results: Of the 80 patients, 40(50%) were in group A; 27(76.5%) males and 13(32.5%) females. The remaining 40(50%) patients were in group B; 20(50%) males and 20(50%) females. The overall age of the sample ranged 36-65 years and 48(60%) had a previous history of heart failure. The mean score of maintenance, management, confidence and overall self-care were significantly higher in group A compared to group B (p<0.05). Conclusions: Nursing self-care educational intervention based on Orem’s theory was found to be highly effective among patients of myocardial infarction and heart failure with respect to their self-efficacy ability. Key Words: Orem’s self-care deficit nursing theory, Self-care ability, Patient’s education, Myocardial infarction, Self-efficacy, Quality of life.